2012
DOI: 10.1007/s00343-012-1065-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of waterborne Fe(II) on juvenile turbot Scophthalmus maximus: analysis of respiratory rate, hematology and gill histology

Abstract: The concentration of Fe(II) is high in some groundwater supplies used in turbot culture, and the toxicity of waterborne Fe(II) is unknown. We investigated the stress responses of juvenile turbot, Scophthalmus maximus, exposed to Fe(II) of different concentrations (0.01, 0.05, 0.1, 0.5, 1, and 2 mg/L) for 1, 7, 14, and 28 d, under the same ambient conditions of other parameters. Changes in respiratory rate, hematological parameters, and gill structure were determined. The results show that waterborne Fe(II) did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Although the observed alterations are not pollutant‐specific, they could be related to previously published results concerning gill alterations caused by experimental exposure to certain pollutants. Iron concentrations close to the values observed in the Tamiš River, in experimental conditions, induced gill damage in the form of hypertrophy, hyperplasia of epithelium, fusions, lifting and rupture of epithelium, haemorrhages and necrosis (Peuranen et al., ; Dalzell and Macfarlane, ; Pandey et al., ; Wu et al., ). Epithelial lifting and swelling, hyperplasia with lamellar fusions, hyperaemia, telangiectasia and alterations in chloride cells were common lesions of gills from fish experimentally exposed to copper (Karan et al., ; Arellano et al., ; Liu et al., ).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Although the observed alterations are not pollutant‐specific, they could be related to previously published results concerning gill alterations caused by experimental exposure to certain pollutants. Iron concentrations close to the values observed in the Tamiš River, in experimental conditions, induced gill damage in the form of hypertrophy, hyperplasia of epithelium, fusions, lifting and rupture of epithelium, haemorrhages and necrosis (Peuranen et al., ; Dalzell and Macfarlane, ; Pandey et al., ; Wu et al., ). Epithelial lifting and swelling, hyperplasia with lamellar fusions, hyperaemia, telangiectasia and alterations in chloride cells were common lesions of gills from fish experimentally exposed to copper (Karan et al., ; Arellano et al., ; Liu et al., ).…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, trace metals induce oxidative stress, hence activating the antioxidant systems, in which depletion in activity of superoxide dismutase, catalase, glutathione S ‐transferase and glutathione in gills is usually noticed (Farombi et al., ). It has been observed that some regressive alterations in the form of rupture of epithelium and epithelial necrosis may be attributed to depletion in activity of these enzymes (Wu et al., ). Coutinho and Gokhale () report distinct differences in gill reactions between common carp ( Cyprinus carpio L., 1758) and Mozambique tilapia [ Oreochromis mossambicus (Peters, 1852)] exposed to secondary sewage effluents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation